PEMBIMBINGAN REFLEKSI PEMBELAJARAN DALAM PKP: SUATU ANALISIS EMPIRIS PADA PROGRAM S1 PGSD-UT - Siti Julaeha (Jurnal Pendidikan, 2009)
This research was conduded through a qualitative approach to find informafion conceming the ability of teachers in doing reflective leaming. Data was gathered through surveys to S1 PGSD students and PKP sypervisors involved in the implementation of the PKP program in Bandung Regional Center Unit. Observasions was also conducted at the location of PKP guidance during tutorial sessions in 2008.1 academic year. Analysis using SWOT method revealed that most teachers already do reflection learning concepts taught in accordance with the guidance of the PKP. The results also revealed that the guidance conducted by the supervisor is still less in providing opportunity for students to share experiences and to practice making scientific work. School facilities, infrastructure and time limited guidance represents a serious challenge for students in archieving the success of leaming reflection. lt is suggested that program S1 PGSD UT to develop altemative models to be used to facilitate supervision of teachers to be able to play a role as active learners, creafive and capable of social adaptation. Through this model teachers are expected to be able to share knowledge and experiences with fellow teachers and supervisors in learning reflection and rn practicing to write a report concerning the results of learning refiection.